2004
DOI: 10.1073/pnas.0402201101
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of nitric oxide in the plasmatic compartment

Abstract: There exist reaction products of nitric oxide (NO) with blood that conserve its bioactivity and transduce an endocrine vasomotor function under certain conditions. Although S-nitrosated albumin has been considered the major species subserving this activity, recent data suggest that additional NO species, such as nitrite, nitrated lipids, N-nitrosamine, and iron-nitrosyl complexes, may contribute. We therefore examined the end products of NO reactions in plasma and blood in vitro and in vivo by using reductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
121
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 51 publications
9
121
0
8
Order By: Relevance
“…More recently, the importance of intravascular hemolysis on NO bioavailability in diseased states including hemolytic anemias like sickle cell disease and paroxysmal nocturnal hemoglobinuria (PNH), thalassemia intermedia, malaria, thrombotic thrombocytopenic purpura, hemolytic uremic syndrome and cardiopulmonary bypass has been elucidated [17][18][19][68][69][70][71][72][73]. It had been thought that cell-free Hb in the blood was mainly present as metHb, but it is in fact mostly oxyHb [19,74]. Reiter and coworkers found that responsiveness to NO administration was blunted by 80% in patients with sickle cell anemia who had plasma Hb concentrations greater than or equal to 6 μM [19].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the importance of intravascular hemolysis on NO bioavailability in diseased states including hemolytic anemias like sickle cell disease and paroxysmal nocturnal hemoglobinuria (PNH), thalassemia intermedia, malaria, thrombotic thrombocytopenic purpura, hemolytic uremic syndrome and cardiopulmonary bypass has been elucidated [17][18][19][68][69][70][71][72][73]. It had been thought that cell-free Hb in the blood was mainly present as metHb, but it is in fact mostly oxyHb [19,74]. Reiter and coworkers found that responsiveness to NO administration was blunted by 80% in patients with sickle cell anemia who had plasma Hb concentrations greater than or equal to 6 μM [19].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the overall chemistry of triiodide that would specifically identify FeNOs has not been described (40)(41)(42)(43)(44)(45); thus, the chemistry behind the putative effects of added reagents (oxidants, reductants, electrophiles, and nucleophiles) that are used to differentiate FeNO, SNO, and nitrite remains unclear. Moreover, few NO standards have actually been tested, and no basis has been provided for asserting that response of these standards captures the general behavior.…”
mentioning
confidence: 99%
“…Moreover, few NO standards have actually been tested, and no basis has been provided for asserting that response of these standards captures the general behavior. Recovery of certain FeNO standards is reported to be as low as zero (40), and the one SNO-Hb standard that has been widely used (an R-structured Hb that contains Ϸ2 NO per tetramer) (40)(41)(42)(43)(44)(45)(46) is neither characteristic of general SNO-Hb reactivity nor of the reactivity of the micropopulation found in RBCs (a valency hybrid, estimated 1 NO per tetramer) (5,47). Furthermore, the claimed effects of added reagents in triiodide assays, including FeCN and NEM (alone and in combination), are not supported, and they, along with the acidic and denaturing conditions of the triiodide assay, can alter the reactivities of SNO and FeNO as well as disrupt the partitioning of NO species within hydrophobic compartments and thus lead to their misidentification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nitric oxide (NO) may bind to albumin, forming S-nitrous-albumin and regulating its plasma levels. (14) In pathological conditions there is no evidence for this potential NO regulation mechanism, but it acts as a vasodilator in the genesis of septic shock. Albumin's antioxidant effects have previously been demonstrated in the context of acute lung injury.…”
Section: In Vitro Effectsmentioning
confidence: 99%